PENATAAN BUKU DAN POJOK BACA PERPUSTAKAAN DI MADRASAH IBTIDAIYAH MANGGARUPI KABUPATEN GOWA - Suban, Alwan; Nursita, Lisa; Halimah, Andi; Musfita; Isnaeni, Nurul; Rahayu, Sri (Department of Islamic Education Management, 2024)
This study aims to organize a library which is a supporting factor for educational success. Qualitative method with a service learning design approach carried out by means of observation, interviews and documentation. The condition of the library has not been able to support student learning at MI Manggarupi. Because the library area does not match the ideal library area. The first step taken is to arrange the books according to class and subject. Through this Service Learning we can understand the arrangement of books and reading corners whose condition is still not in accordance with library standards in general. The results of this service learning are that books are arranged according to class and subject, filled with books that have been stamped according to the applicable school curriculum, damaged reading corner tables are replaced.